Resenha do livro: Nietzsche/Deleuze Natureza/ Cultura - Linguagens Geográficas, Membros do Grupo de Pesquisa (ENTRE-LUGAR, 2012)
LINS, Daniel; OLIVEIRA, Nilson; BARROS, Roberto (orgs.). Nietzsche/Deleuze Natureza/Cultura. São Paulo: Lumme Editor, 2011.